Developing Student-Created Case Studies to Enhance Diversity Learning Outcomes and Strengthen Bhinneka Tunggal Ika Values - Eva Ardilla; Sri Rahayu Pudjiastuti; Suidat Suidat (PUSAKA: Journal of Educational Review, 2026)
This study aims to obtain empirical data on the development of the Student Created Case Studies method based on image media to improve student learning outcomes on community diversity and participation in strengthening the motto of Bhinneka Tunggal Ika at SMPN 1 Tamansari, Bogor Regency. This study addresses a research gap in the limited use of student-centered, image-based case study methods in Civics learning that explicitly integrate the values of Bhinneka Tunggal Ika. The novelty lies in combining the Student Created Case Studies approach with visual media to promote active and contextual learning. The method used is Research and Development (R&D) adapted from Sugiyono. The subjects were 28 seventh grade students, with peers as key informants. The study was conducted in July–August of the 2024/2025 academic year. Data were collected through tests and questionnaires, with instruments tested for validity and reliability. Needs analysis and expert validation by material and media specialists were also conducted. The results showed that the developed method improved student learning outcomes. The material feasibility score reached 93.18%, and the media feasibility score was 91.67%, both categorized as very feasible. Thus, this method is effective and suitable for enhancing students’ understanding and participation in diversity values.